Does Identity Affect Labor Supply? - Oh, Suanna (American Economic Review, 2023)
How does identity influence economic behavior in the labor market? I investigate this question in rural India, focusing on the effect of caste identity on job-specific labor supply. In a field experiment, laborers choose whether to take up various job offers, which differ in associations with specific castes. Workers are less willing to accept offers that are linked to castes other than their own, especially when those castes rank lower in the social hierarchy. Workers forgo large payments to avoid job offers that conflict with their caste identity, even when these decisions are made in private. (JEL C93, D91, J15, J22, O12, Z13)